Ciclo de vida do sistema produto-serviço (pss): proposição de diretrizes para gestão das etapas na fase de uso - Cardone, Juliane Chaves (Universidade do Vale do Rio dos Sinos, 2017)
The offer of a Product-Service System (PSS) aims to provide value-in-use from integrated solutions that optimize customer processes. From the perspective of the life cycle of a PSS, the literature lacks studies that explore the use scope, aspects such as: management, contracts, relationships in corporate contexts, integration, co-production, failures and their risks. This study aims to contribute with the literature of PSS proposing guidelines that can support the managers of a PSS supplier in the management phase of the use of the life cycle. The research, considered as a single case study, was carried out from the point of view of the PSS supplier through interviews with managers, who are knowledgeable about the management strategies offered by the company and have mastery of the mentioned aspects. The results of the research suggest management difficulties in the usage phase, due to the excess of contractual improvisations, the limitations stemming from the fragile relationship with the client, lack of integration between the parties, the co-production benefiting only one side and management failures that pose risks to the company. However, the stimulus for the decentralization of the management contributes positively to the development of a new perspective of the PSS life cycle and that favours, besides the managerial sphere, the actors involved in this management. The proposed guidelines focus primarily on relationship and integration and aim to improve the performance of the use phase of the PSS life cycle.
Keywords: Sistema produto serviço; Gestão de PSS; Ciclo de vida de PSS; Contratos; Integração; Relacionamento; Product service system; PSS Management; PSS life cycle; Contracts; Relationship; Integration; ACCNPQ::Engenharias::Engenharia de Produção